Caribbean Fruit Fly, Anastrepha suspensa (Loew) (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr.; John B. Heppner; Thomas R. Fasulo; James L. Nation (EDIS, 2004)
The Caribbean fruit fly, Anastrepha suspensa (Loew), has also been called the Greater Antilliean fruit fly, the guava fruit fly and the Caribfly. It is a near relative of the Mexican fruit fly, Anastrepha ludens (Loew), and is one of several species of fruit flies which are indigenous to the West Indies and the larvae of which attack several kinds of tropical and subtropical fruits. This document is EENY-196 (originally published as DPI Entomology Circulars 38 and 260), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2001.